2023
DOI: 10.1161/hypertensionaha.123.21684
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Oxidative Stress–Mediated Reductions in Microvascular Endothelial Function in Young Adult e-Cigarette Users

Kristen M. Halstead,
Elizabeth M. Wetzel,
Josalyn L. Cho
et al.

Abstract: Background: Chronic e-cigarette (EC) use is reported to decrease vascular endothelial function. However, the mechanism(s) mediating this reduction remain unclear. In this study, we examined endothelium- and NO-dependent dilation, and the role of oxidative stress in attenuating these responses, in healthy young EC users (n=20, 10 males/10 females) compared with healthy controls (n=20, 10 males/10 females). We hypothesized that EC would have reduced endothelium- and NO-dependent dilation and administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…In addition, other critical mediators including prostaglandins and EDHF [ 52 ] are also involved in the endothelial-mediated response of the small vessels and may be also impaired in those that consume e-cigarettes, as suggested by our data from the PORH, LTH and iontophoresis with ACh reactivity tests. Our results support reduced endothelial-dependent microvascular function which was described in another cohort of users of e-cigarettes [ 19 ]. Recently, a study completed in a preclinical model exposed to e-cigarette vapor has also identified impaired endothelial-independent mechanisms [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, other critical mediators including prostaglandins and EDHF [ 52 ] are also involved in the endothelial-mediated response of the small vessels and may be also impaired in those that consume e-cigarettes, as suggested by our data from the PORH, LTH and iontophoresis with ACh reactivity tests. Our results support reduced endothelial-dependent microvascular function which was described in another cohort of users of e-cigarettes [ 19 ]. Recently, a study completed in a preclinical model exposed to e-cigarette vapor has also identified impaired endothelial-independent mechanisms [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is well established that traditional combustible tobacco usage is associated with worse endothelial function and lowered nitric oxide levels [ 49 51 ]. Preliminary evidence in the microvasculature [ 19 ] and other vascular beds [ 12 ] supports that e-cigarette use also leads to a reduction of this mediator [ 12 ]. Our results align with previous observations and support that regular consumers of e-cigarettes exhibit a reduction of this essential vasodilator also in the microcirculation, as evaluated through LTH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no significant effects were observed in male vapers. 14 Of course, vaping/smoking cessation is and will remain the most potent approach to prevent cardiovascular and respiratory side effects.…”
Section: Are There Sex-specific Effects Of Nicotine On Blood Pressure?mentioning
confidence: 99%